2006
DOI: 10.1080/07315724.2006.10719553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Viscous Fiber Bar on Postprandial Glycemia in Subjects with Type 2 Diabetes

Abstract: The incorporation of VF into a crispy bar provided a means to improve blood glucose levels by reducing postprandial glucose, insulin, and C-peptide responses in subjects with type 2 diabetes. Though associated with some GI symptoms, VF may have application in improving the postprandial glycemic response in people with diabetes attempting intensive glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…We also demonstrated that adding a soluble fiber supplement (10 g/d) to the normal diet for 6 wk resulted in a decrease in HbA1c in patients with T2D (13). The beneficial acute effect of soluble fiber intake (psyllium, b-glucan, and guar) on postprandial plasma glucose response was observed in patients with diabetes (14)(15)(16) after the consumption of a high-fiber meal (17) or single beverages or foods (18,19).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…We also demonstrated that adding a soluble fiber supplement (10 g/d) to the normal diet for 6 wk resulted in a decrease in HbA1c in patients with T2D (13). The beneficial acute effect of soluble fiber intake (psyllium, b-glucan, and guar) on postprandial plasma glucose response was observed in patients with diabetes (14)(15)(16) after the consumption of a high-fiber meal (17) or single beverages or foods (18,19).…”
Section: Introductionmentioning
confidence: 81%
“…Other studies conducted in patients with T2D have evaluated the acute insulin response after consuming foods containing fiber but without testing different sources of fibers as we did (15)(16)(17)(18)(19). Only one study (17), conducted in a small sample of 8 patients with T2D, evaluated glucose and insulin responses after consuming a common meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line of research, studies done by Flamammg et al (2006) showed a lower glycemic and insulin response in individuals who consumed cereal bars enriched with soluble fiber (guar gum) as compared to those who consumed commercial bars low in fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Cohort studies have consistently shown reductions in risk for diabetes and cardiovascular disease (CVD) in those who consumed high-fiber foods and larger amounts of whole grain cereals [52][53][54][55][56][57][58] . Controlled trials have also suggested that there may be a benefit for increased fiber in terms of improved glucose tolerance [59][60][61][62] . Viscous fibers have been shown to slow the rate of nutrient absorption [63] , and this aspect of metabolism has been demonstrated to reduce insulin requirements, possibly offering a reason why high-viscous fiber diets may be effective [64,65] .…”
Section: Fiber and Whole Grainsmentioning
confidence: 99%